EXPERIMENTAL VERIFICATION OF SOCIAL ACTIVITY OF JUNIOR SCHOOLCHILDREN IN EXTRACURRICULAR ACTIVITIES - Potapchuk, Teniana; Klepar, Maria (Educological discourse, 2020)
The article considers social activity, which is a condition of self-determination of the individual in society and conscious regulation of behavior; manifests itself in various spheres of human life: labor, socio-political, educational and leisure, social and domestic. It is realized in various forms not only as an individual, but also as a group or collective, aimed at realizing the capabilities and potential of certain social groups. Social activity can be considered as a creative, productive, or non-creative, reproductive process, as it is manifested in creativity, acts of will, communication. The integral characteristic of social activity reflects the active life position of the person which is shown in its principledness, defense of own positions, views at the decision of social questions; human ability to make socially significant changes in life, experience, material and spiritual culture. It is from the active life position of the individual depends on a person’s ability to make socially significant changes in social development. With the help of the method of incomplete sentences, the knowledge about the essence of such socially significant qualities as social responsibility, social activity, tolerance, solidarity in junior schoolchildren was clarified. Thus, the purpose of the article is to theoretically substantiate the key concepts of "social activity", "social interaction" and experimental testing of socially significant qualities such as social responsibility, social activity, tolerance, solidarity in junior high school students. The article uses methods: analysis, systematization and generalization of scientific literature in order to clarify the state of development of the research problem and clarify the conceptual apparatus, the method of incomplete sentences was used to collect empirical material. The concept of educating social activity of junior schoolchildren in extracurricular activities remains undeveloped. We consider it promising to study the relationship between educational and extracurricular activities in the education of social activity of junior students.